The Effectiveness of Authentic Learning Materials to Enhance Kayuh Baimbai Characters - Muhammad Hafiz Ridho; Mustika Wati; Suryajaya Suryajaya (Jurnal Ilmiah Pendidikan Fisika, 2025)
The limited availability of science learning materials containing authentic learning and students' low academic performance served as the background for this research. This research generally aims to describe the effectiveness of science learning that contains authentic learning on vibration, waves, and sound. This research is classified as research and development using the ASSURE model, with 23 eighth-grade students from one of the public junior high schools in Banjarmasin as the test subjects. Data were obtained from character observation sheets, which were then analyzed by averaging the values of each indicator and comparing them with the effectiveness criteria. The results showed that the effectiveness was classified as effective, with a value of 68.34 for the Kayuh Baimbai characters. The research concludes that the developed science learning material with authentic content on vibration, waves, and sound was adequate to be used in educational activities to enhance students’ Kayuh Baimbai characters. This research implies that the implementation of authentic learning materials can serve as an effective strategy for character education in science learning, provided that instructional time efficiency is carefully considered.